Early processing of emotional faces in a Go/NoGo task: lack of N170 right-hemispheric specialisation in children with major depression - Grunewald, Madlen; Brandeis, Daniel (Journal of neural transmission, 2015)
Emotionally biased information processing towards sad and away from happy information characterises individuals with major depression. To learn more about the nature of these dysfunctional modulations, developmental and neural aspects of emotional face processing have to be considered. By combining measures of performance (attention control, inhibition) in an emotional Go/NoGo task with an event-related potential (ERP) of early face processing (N170), we obtained a multifaceted picture of emotional face processing in a sample of children and adolescents (11-14 years) with major depression (MDD, n = 26) and healthy controls (CTRL, n = 26). Subjects had to respond to emotional faces (fearful, happy or sad) and withhold their response to calm faces or vice versa. Children of the MDD group displayed shorter N170 latencies than children of the CTRL group. Typical right lateralisation of the N170 was observed for all faces in the CTRL but not for happy and calm faces in the MDD group. However, the MDD group did not differ in their behavioural reaction to emotional faces, and effects of interference by emotional information on the reaction to calm faces in this group were notably mild. Although we could not find a typical pattern of emotional bias, the results suggest that alterations in face processing of children with major depression can be seen at early stages of face perception indexed by the N170. The findings call for longitudinal examinations considering effects of development in children with major depression as well as associations to later stages of processing.